Mechanisms of Access and Power in Strengthening the Performance of Marine Ecotourism Management Institutions - Aini, Nur; Satria, Arif; Sri Wahyuni, Ekawati (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
The objective of this research is to analyze: 1) The distribution of benefits of Kampung Arborek’s toursim; 2) The access and power mechanism of the community who manages the ecotoursim in obtaining, maintaining, and controlling the resources; 3) and the performance of the power of the management institution of Kampung Arborek marine ecotoursim. The approach used in the research is the qualitataive approach. The techniques used to collect the data are through observation, documentation, interviews, focus group discussions, and secondary data collection. The results of this research show that the distribution of benefits that is obtained by the community who manages the ecotourism is an increase and more stable income compared to their previous income as fishermen. The distribution of benefits that was felt by the community who manages the ecotourism is inseparable from the access and power mechanism that they own. Through the bundle of power such as technology, capital, market, workforce, knowledge, authority, social identity and social relation, are used by the ecotoursim management community to obtain and maintain access towards resources. Through this bundle of power they are also capable of strengthening the performance of the marine ecotourism institution’s managment in Kampung Arborek. Therefore, equality in access and power for the community is needed to open new oppurtunities to obtain benefits from managing the ecotourism and also reinforcement of the performance of the institution’s management.